CDC20 and CCNB1 Overexpression as Prognostic Markers in Bladder Cancer - Hatice Sevim Nalkiran; Ilknur Biri; Ihsan Nalkiran; Hakki Uzun; Sumeyye Durur; Recep Bedir (Diagnostics)
Background: Bladder cancer (BC) is one of the ten most common cancers worldwide, with a high recurrence rate and significant variation in clinical outcomes based on tumor grade and stage. This study aimed to investigate the gene expression profiles at different cancer stages to assess their potential prognostic value. Methods: RNA was extracted from paraffin-embedded BC tissues and the gene expression levels of CDC20 and CCNB1 were analyzed using qRT-PCR. A total of 54 BC patient samples were included in the analysis and categorized into low-grade (LG) (n = 23) and high-grade (HG) (n = 31) tumors, as well as stages pTa, pT1, and pT2. Results: CDC20 gene expression was significantly higher in the HG group (mean fold-change: 16.1) compared to the LG group (mean fold-change: 10.54), indicating a significant association with tumor grade (p = 0.039). However, no significant differences were observed in CDC20 expression across the cancer stages. For CCNB1, while gene expression was significantly elevated in higher-stage tumors (pT2 vs. pTa; p = 0.038), no significant association was found between CCNB1 expression and tumor grade. Survival analysis revealed that increased CCNB1 expression and advanced cancer stage were associated with poorer overall survival, whereas no significant impact of CDC20 expression or tumor grade on survival was observed. Correlation analysis indicated a positive relationship between CDC20 expression and tumor grade (r = 0.284, p = 0.038) and between CCNB1 expression and tumor stage (r = 0.301, p = 0.027). Conclusions: Our findings suggest that CDC20 overexpression is linked to higher tumor grades, while CCNB1 overexpression is associated with more advanced cancer stages in BC. These results underscore the potential utility of CDC20 and CCNB1 as biomarkers for tumor prognosis and as therapeutic targets. Further studies with larger cohorts are needed to validate these findings and better understand the molecular mechanisms driving BC progression.